The Influence of the Work Environment, Commitment and Personality of UMKM on the Loyalty of Human Resources Through The Performance of UMKM in Klambir V Kebun Village - Sebayang, Saimara AM; Ario, Firman; Taufik, Mahful (Journal of Community Research and Service, 2023)
This study aims to analyze the effect of the work environment, commitment, personality of  UMKM  on HR loyalty through UMKM performance. The research was conducted in Kelambir Lima Kebun Village, Hamparan Perak District, Deli Serdang Regency. This type of research is associative research with quantitative descriptive method. The number of samples studied in this study were 50 respondents who were UMKM actors. Data analysis was carried out through PLS-SEM using the SmartPLS v. program. 3. The results of direct effect research show that the work environment, commitment and personality of  UMKM  have a positive and significant effect on UMKM performance. The personality of UMKM has a positive and significant effect on HR loyalty. The work environment has no positive and insignificant effect on HR loyalty. UMKM performance has a positive and significant effect on HR loyalty. While the results of the indirect effect research show that the work environment, commitment and personality of  UMKM  have a positive and significant effect on HR loyalty through UMKM performance.